β-Glucan-modified nanoparticles with different particle sizes exhibit different lymphatic targeting efficiencies and adjuvant effects - Wen Guo; Xinyue Zhang; Long Wan; Zhiqi Wang; Meiqi Han; Ziwei Yan; Jia Li; Ruizhu Deng; Shenglong Li; Yuling Mao; Siling Wang (Journal of Pharmaceutical Analysis)
Particle size and surface properties are crucial for lymphatic drainage (LN), dendritic cell (DC) uptake, DC maturation, and antigen cross-presentation induced by nanovaccine injection, which lead to an effective cell-mediated immune response. However, the manner in which the particle size and surface properties of vaccine carriers such as mesoporous silica nanoparticles (MSNs) affect this immune response is unknown. We prepared 50, 100, and 200 nm of MSNs that adsorbed ovalbumin antigen (OVA) while modifying β-glucan to enhance immunogenicity. The results revealed that these MSNs with different particle sizes were just as efficient in vitro, and MSNs with β-glucan modification demonstrated higher efficacy. However, the in vivo results indicated that MSNs with smaller particle sizes have stronger lymphatic targeting efficiency and a greater ability to promote the maturation of DCs. The results also indicate that β-glucan-modified MSN, with a particle size of ∼100 nm, has a great potential as a vaccine delivery vehicle and immune adjuvant and offers a novel approach for the delivery of multiple therapeutic agents that target other lymph-mediated diseases.